Sei sulla pagina 1di 70   0.1

Algebraic techniques See
See
C3
C3
and
and
C4
C4 for revision.
for revision.
This section provides
This section provides

You can simplify algebraic fractions by using common denominators. FP2
 EXAMPLE Simplify 4 + 3 x + 1 x + 2 •••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••• Rewrite the fractions so that they each have denominator (x + 1)(x + 2): 1 4 3 4 ≡ ( x + 2 ) 3 ( x + 1 ) + x + + 2 1 x + ≡ ( x 4 ( + x 1 )( x + 2 ) )( 23 ++ x + ( x 1 ) + 1 )( x + 2 ) Add the numerators: ( x + 1 )( x + 2 ) Simplify: ≡ 7 x + 11 (x + 1 )(x + 2 ) Hence 4 + 3 ≡ 7 x + 11 x + 1 x + 2 ( x + 1 )( x + 2 )

background knowledge

background knowledge

for Chapters 1, 2, 3 and 6.

for Chapters 1, 2, 3 and 6.

ºº meansmeans ‘is‘is equivalentequivalent to’.to’.

You can split an algebraic fraction into its partial fractions.

 EXAMPLE Express ( x 5 + x − 1 1 ) as the sum of partial fractions. 1 )( x − •••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••• Write the fraction in the required form: 2 5 x − 1 A B ≡ + ( x )( 11 +− x ) ≡ ( x + ( Ax 1 ) ( x − 1 )( 1 −+ Bx ) + 1 ) ( x + 1 )( x − 1 ) Compare numerators: 5x - 1 º A(x - 1) + B(x + 1) Substitute appropriate values of x into this identity to find A and B: When x = 1, i.e. 4 = A(1 - 1) + B(1 + 1) 4 = 2 B so B = 2 Similarly, when x = -1 A = 3 Hence, in partial fractions, 5 x − 1 ≡ 3 + 2 ( +− )( 1 xx 1 ) ( x + 1 ) ( x − 1 )

AA andand BB areare constants.constants.

Denominators Denominators are are equal equal so so the the

numerators numerators must must also also be be equal. equal.

You You could could also also find find A A and and B B

by by comparing comparing coefficients coefficients in in

the identity

the identity

5x - 1 º A(x - 1) + B(x + 1)

5x - 1 º A(x - 1) + B(x + 1)

0 Background knowledge for unit FP2

You can rearrange an expression involving an algebraic fraction.

 EXAMPLE 2 x + 1 Make x the subject of the equation y = x − 1 •••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••• Multiply both sides of the equation by the denominator (x - 1): 3 2 x + 1 so y(x - 1) = 2x + 1 y = x − 1 Expand the bracket and collect terms in x: yx - 2x = y + 1 i.e. (y - 2)x = y + 1 so x = y y + 1 − 2

You can expand expressions of the form (1 + x) n , where n is not a positive integer, by using the binomial theorem. 1
a Expand (1
+
2
x
)
2
in ascending powers of x up to and
including the term in x 2 .
1
b By substituting x =
4 into your expansion, estimate the
value of
1.5.
••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••
n n − 1
(
)
n
2
a Apply the binomial theorem (
1
+
x
)
=+
1
nx
+
x
+
:
2
!
( )(
1
1
)
1
(
1
2
)
2
2
2
(
12
+
xxx
)
=+
1
()
2
+
()
2
+
2
2 !
1
2
=+1
x
x
+
2
1
1
2
b Substitute x = 1 4 into the approximation ()12
+
x
2
≈+−xx
1
:
2
1
2
( ))
1
2
1
1
)
( 12
+
≈+
1
4
4
1 2 (
4
i.e.
1.5 ≈ 1.21875
Hence
1.5 ≈ 1.22 (to 2 decimal places)
EXAMPLE
4

     

1

1

+

+

2

2

(

(

1 1

4

4

)

)

     

1 1

2 2

=

= FP2
15
15.
.

0 Background knowledge for unit FP2

You can use the binomial theorem to find the expansion of an algebraic fraction. FP2
 EXAMPLE Express x 1 − x as a series of ascending powers of x up to and including the term in x 4 . •••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••• 5 x = x ( 1 − x ) − 1 1 − x Use the binomial theorem to expand (1 ( 1 − ) − 1 =+ 1 ( − 1 )( ) + ( − 1 )( − 2 − x ): 1 − ) () 23 + − − − () ( )( 123 )( ) + x =+1 − x xx + 2 + x 3 2 ! + − x 3 ! − x Multiply through by x: − 1 23 x()1 − x = =+xx x(1 ++ xx + x 234 + x + x + + Hence x 1 − x =+ xx 234 + x + x + ) Exercise 0.1 1 Simplify these expressions. Factorise your answers as far as possible. a 2 4 b 3 1 + − x + 2 x − 1 x − 4 x + 1 c x x + 3 + x x + 1 d 2 x + x + 1 1 + 2 x 1 − 1 x 1 e − x + 4 x + 1

2 Express these fractions in partial fractions.

a

c

4

x +

3

(

x

+

5

x

2

)(

6

x

2

x

4

3

)

b

d

x + 2

(

x

+

4)(

x

+

2

x

7

3)

(

2

x

1

)(

x

+

2

)

The expansion is valid

The expansion is valid

for

for

-1 < x < 1.

-1 < x < 1.

3 Rearrange these equations to make x the subject.

a

c

y =

y =

3 x

x

+ x + 1

x

2

2

1

1

b

d

y

=

y =

2

x

+ 3

1

4

x

3 x

3

x +

1

0 Background knowledge for unit FP2

4 Use the binomial theorem to express these functions as a series of ascending powers of x up to and including the term in x 3 .

a (1 + x) -1

b

1

( 1

+

3

2

3

x)

2

3 )

x

c (1

5 It is given that (1

+ x

)

1

2

=+

1

a Find the expansion of (1

1

2

+

1

xx

8

2

+

1

16

x

3

4 )

x

1

2

in ascending powers of

x up to and including the term in x 3 .

1

b By substituting the value x = 8 into your expansion in

part a estimate the value of 2.

Replace x with 4x in the

Replace x with 4x in the

given expansion.

given expansion.

6 Express these functions as ascending powers of x up to and including the term in x 3 . x
a
(1
+ 2x) 2
x
− 1
b
1 + x
4
x +
3
c (
1312
+
x
)( −
x
) FP2 0.2

Inequalities See C2 for revision.
See
C2
for revision.

You can use a graphical approach to solve an inequality.

This is background knowledge

This is background knowledge

for Chapter 1.

for Chapter 1. Use a graphical approach to solve the inequality x 2 - 5x + 4 < 0
••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••
Sketch the graph with equation y = x 2 - 5x + 4:
y
x
1
4
The inequality x 2 - 5x + 4 < 0 has solution 1 < x < 4.
EXAMPLE
1

x 2 - 5x + 4 º (x - 1)(x - 4)

x

5x + 4 º (x - 1)(x - 4)

2 -

The graph cuts the x-axis when y = 0

The graph cuts the x-axis when y = 0

i.e when (x - 1)(x - 4) = 0

i.e when (x - 1)(x - 4) = 0

The graph has roots x = 1, x = 4.

The graph has roots x = 1, x = 4.

x 2 - 5x + 4 < 0 is satisfied by

x 2 -

5x + 4 < 0 is satisfied by

values of x for which the graph

values of x for which the graph

y = x 2 - 5x + 4 lies on or below

y = x

- 5x + 4 lies on or below

2

the x-axis.

the x-axis. FP2

You can also solve an inequality by using algebra.

EXAMPLE

2

Use algebra to solve the inequality x 2 + 3 4x

••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••

Express the inequality in the form f(x) 0 where f(x) is factorised:

x 2 - 4x + 3 0

i.e.

(x - 1)(x - 3) 0 Solve the equation f(x) = 0 where f(x) = (x - 1)(x - 3):
(x - 1)(x - 3) = 0
for x = 1, x = 3
Use appropriate values of x to find the sign of f(x) in the intervals
x < 1, 1 < x < 3, x > 3:
f( x ) > 0
f( x ) < 0
f( x) > 0
x < 1
1 < x < 3
x > 3
e.g.
f(0) = 3 (>0)
f(2) = -1 (<0)
f(4) = 3 (>0)
Hence the inequality x 2 + 3 4x has solution x 1, x 3.

1

3 x

The inequality is satisfied for

The inequality is satisfied for

values of x for which f(x) 0.

values of x for which f(x) 0. Remember Remember to to include include x x = = 1 1 and and

x x

= = 3 3 in in the the solution solution of of f(x) f(x) 0. 0.

0 Background knowledge for unit FP2

Exercise 0.2

1 Use any appropriate technique to solve these inequalities.

a x 2 - 5x + 6 0

b 2x 2 + 5x - 3 < 0

c 4x 2 - 1 > 0

d x 2 - 7x + 10 5 - x

e x 2 - 3x + 2 2x + 8

f 2x 2 - 2x - 12 > 3 - x

2 Solve the inequality x 2 - 2x - 4 < 0 Give your answers in surd form.

3 Use a graphical approach to show that the inequality

x 2 - 6x + 10 < 0

has no solution.

4 Solve these inequalities.

a x(x + 2)(x + 4) > 0

b (x + 1)(x 2 - 9) 0

c x 3 + 2x 2 + x < 0 FP2 0.3

Modulus and exponential graphs See C3 for revision.
See
C3
for revision.

To sketch a graph with equation y = |f(x)|:

sketch the graph y = f(x) reflect the ‘negative’ part of your graph in the x-axis.

This is background knowledge

This is background knowledge

for Chapters 1, 4 and 5.

for Chapters 1, 4 and 5. Sketch the graph with equation y = |x 2 - 4|
••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••
Sketch the graph with equation y = x 2 - 4, drawing the part
of the graph that lies beneath the x-axis as a broken line.
Most graphical calculators
Most graphical calculators
can plot the graph of a
can plot the graph of a
modulus function.
modulus function.
Reflect the dotted section in the x-axis:
Look for the ABS key.
Look for the ABS key.
(The reflected part has equation y = 4 - x 2 )
y = |x 2 – 4|
y
The y-axis crossing point (0, 4) is
The y-axis crossing point (0, 4) is
the reflection of the point (0, -4)
the reflection of the point (0, -4)
y = x 2 – 4
y = x 2 – 4
in the x-axis.
in the x-axis.
y = 4 – x 2
4
Label each section of the graph
Label each section of the graph
with its equation.
with its equation.
O
x
–2
2
This is the ‘negative’ part of
This is the ‘negative’ part of
the graph.
the graph.
–4
EXAMPLE
1
FP2

You can sketch the graph with equation y = Ae kx , where A and k are constants.

EXAMPLE

2

Sketch the graph with equation y = 3e -2x

••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••

The graph with equation y = 3e -2x resembles that with equation y = e -x y
y = 3e –2 x
3
O
x

When x = 0, y = 3e -2(0) = 3,

= 3,

When x = 0, y = 3e

-2(0)

i.e. the y-intercept of the

i.e. the y-intercept of the

graph is 3.

graph is 3.

The The positive positive x-axis x-axis is is an an

asymptote asymptote to to the the graph. graph.

0 Background knowledge for unit FP2

Exercise 0.3

1 On separate diagrams, sketch the graphs with these equations.

Label all axis-crossing points with their values and the sections of the graph with their equations.

a y = |2x + 1|

b y = |2 - 3x|

c y = |x 2 + 4x + 3|

d y = |3x - 2x 2 |

2 On separate diagrams, sketch the graphs of these equations.

Label all axis-crossing points with their values, giving answers in surd form where appropriate.

a y = |x 3 - 1|

b y = |(x + 3) 2 (x - 1)|

c y = |(3 - x)(x 2 - 2)|

3 On separate diagrams, sketch the graphs with these equations.

a y = 2e 3x

b y = -e -x

c y = 3e x + 1

d y = 3 - e -2x FP2

4 On separate diagrams, sketch the graphs with these equations.

a y = |e -x - 1|

b y = |e x - 2|

5 Given that x < e x for all x 0,

a show that x 2 < e 2x for all x 0

b deduce that xe -2x is approximately zero for large positive values of x. 0.4

Trigonometry See C3 for revision.
See
C3
for revision.

This is background knowledge

This is background knowledge

You can use a trigonometric identity to simplify an equation. You should know these identities:

for Chapters 3 and 7.

for Chapters 3 and 7.

cos2

q

cos

22

qq

sin

sin 2q 2sinqqcos

tan

2

q

+ 1

2

sec

q

2cos

2

q −≡

112sin

2

tan 2

q

2 tan 1 tan

q

2

q

1 + cot q cosec q

2

2

q

sin sin

2 q

2

q + cos

+ cos 2 q º 1

q º 1

2

tan

tan

q

q

sin

sin

q

q

cos

cos

q

q

(for cos q ¹ 0)

(for cos q ¹ 0) FP2
 EXAMPLE 1 Solve the equation cos 2q + cos q = 0 for 0 q p. Give answers in exact form. •••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••• Replace cos 2q with 2cos 2 q - 1 in the equation: cos 2q + cos q = 0 2cos 2 q - 1 + cos q = 0 i.e. (2cos q - 1)(cos q + 1) = 0 so Hence cos q = 1 2 or cos q = -1 cos q = 2 when q = p 3 1 1 cos q = -1 when q = p 1 Hence cos2q + cosq = 0 has solutions q = p p for 0 q p. 3 ,

equation in cos q.

equation in cos q.

SinceSince 00 qq pp

(i.e. in terms of p).

(i.e. in terms of p).

You can use identities to reduce the number of different trigonometric functions in an expression.

EXAMPLE

2

Express sin 2q cos q in terms of sin q only.

••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••

Use the double-angle identity sin 2q º 2 sin q cos q :

sin 2q cos q º (2 sin q cos q)cos q

º 2 sin q cos 2 q

º 2 sin q(1 - sin 2 q)

Hence sin 2q cos q º 2sin q(1 - sin 2 q)

sin 2q cos q involves two

sin 2q cos q involves two

trigonometric functions.

trigonometric functions.

cos cos

2 q º 1 - sin 2 q

q

2

q º 1 - sin

2

RHSRHS dependsdepends onlyonly onon sinsin qq

Exercise 0.4

1 Solve these equations. Give answers in exact form.

a

b

c

d

 sin 2q = cos q for 0 q p sin 2q = tan q for 0 q p cos 2q = 3 sin q + 2 for -p q p 3cos 2q = cos q

for 1

2

pq

p

2

1 2 Express 3sin q + cos q in the form R sin(q + a),

a

where R > 0 and 0 < a <

b

Hence solve the equation 3sin q + cos q = 1

for 0 q p

1 2 p is exact.

0 Background knowledge for unit FP2

3 Express these functions in the required form.

a cos 2q sin q

b sin 2q sin q in terms of cos q only

c as a function of sine only

d cos 4 q - sin 4 q

in terms of sin q only

cos 2q sin 2q

as a function of cosine only

4 The diagram shows an isosceles triangle ABC, where AB = AC = k and CAB = 2q radians.

a Show that BC = 2k sin q.

b Given that triangle ABC has area 3

4

2

k , find, in terms

of k, the two possible lengths of BC.

5 Use a graphical approach to verify that

a cos(-q) º cos q

b sin(-q) º -sin q

c tan -1 (-q) º -tan -1 q FP2
C C
k k
2 2
i
i
A A
B
B
k k 0.5
1.1
Differentiation
You need to know these standard results of differentiation:
See C3
See
C3
and
and C4 for revision.
C4
for revision.
This is background knowledge
This is background knowledge
d
d ( e
ax
) =
ax
a e
(lnax) = 1
for Chapters 4, 5, 6 and 7.
for Chapters 4, 5, 6 and 7.
d
x
dx
x
d
dx d (sinax) = acosax
( cosax
) = −
asinax
dx FP2

where a is a non-zero constant.

You can use rules and standard results of differentiation to find the first and second derivatives of a function.

 EXAMPLE 2 If y = xe 2x find d d y and d y x d x 2 . •••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••• Use the product rule, d ( uv ) = u d v + v d u , to find d y : 1 d x d x d x d x y = xe 2x so d y x d = ( x 2 e 2 x ) + e 2 x 1 () Factorise: = (2 x + 1) e 2 x Use the product rule on d y to find d 2 y : d x d x 2 d y x d = (2 x +1) e 2 x so d d 2 y 2 x 2 =+( x ( ) 12 e 2 x ) + e 2 x 2 ( ) Hence d y =+(21) 2 x and 2 = 2224( e x x +=) 2 d y = 4 2 x ()+1 e 2 x ()+1 x d x x e d 2 x e x

You can use a trigonometric identity to simplify the differentiation process.

 EXAMPLE Find f ¢(x) when f(x) = sin x(cos x + 1) •••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••• f( ) x = sin ( xx cos + 1 ) 2 = sin xx cos + sin x = 1 2 sin 2 x Use the chain rule, d + ( 1 sin x sin2 x ) = 2cos 2 xx = cos 2 : dx 2 1 2 ( ) f′(x) = cos2xx+ cos

These include the chain, product

These include the chain, product

and quotient rules.

and quotient rules.

d d

dx dx

( (

e

e

2

2

x

x

) ) =

=

2e

2e

2

2

x

x

using using the the chain chain rule. rule.

ff ¢¢((xx)) isis thethe firstfirst derivativederivative ofof f(f(xx).).

UsingUsing sinsin 22xx ºº 2sin2sin xx coscos xx

You can use the chain rule to differentiate implicitly.

0 Background knowledge for unit FP2

 EXAMPLE Find an expression for d dx ( 2 ). y •••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••• Use the chain rule: 3 d () = 2 d ()× 2 d y d d 2 2 2 d x y d y = 2y y d y x d d x dy dy ( ( y y ) = 2 ) = 2 is being y since y 2 is being y since y differentiated with respect to y. differentiated with respect to y. Exercise 0.5 1 Find d y d x for these equations. Simplify each answer as far as possible.

a

c

y = e x sin x

y =

x + 1

e

x

b

d

y = ln(1 + x 2 )

y = ln(sin 2 x)

2 Find the exact maximum value of these functions over the given interval. You should show each answer is a maximum.

a f(q) = sin q + cos q

b f(q) = sin 2 q - 1

for 0 q p

for 0 < q

1

2 p FP2

3 Using trigonometric identities, or otherwise, differentiate these equations. Simplify each answer as far as possible.

a y = sin x cos 2x + cos x sin 2x

b y = 4cos 2 x sin 2 x

c y = (1 - 2sin 2 2x) 2

4 Use implicit differentiation to find an expression for these derivatives.

d

a dx

(

y

3

)

b

d

dx

( xy

2 )

c

d

d x

(

x

2

d y

d x

)

5 If y = ux, where u is a function of x,

a find an expression for

d y

d x .

b Hence show that d

d

y

2

=

2

d

u

2

d u

2

x

d

x

d

2

x

+ x 0.6

Integration

See

See C3
C3

and

and C4
C4

for revision.

for revision.

You need to know these standard integrals:  1

ax

d

x

=

cos ax

()d

1

a

x

ln

=

+

xc

1

a

sin ax

() +

c  ed

ax

x

=

1

a

d

sin(ax) x

e

ax

=

+

1

a

c

(

cos ax

) +

c

This is background knowledge

This is background knowledge

for Chapters 4 and 7.

for Chapters 4 and 7.

aa isis aa non-zeronon-zero constant.constant. FP2

You can use the rules and standard results of integration to integrate more complicated functions.

 EXAMPLE 1 Using the substitution u = 2x 2 , find x cos(2xx) 2 d •••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••• Replace the term 2x 2 with the variable u: x cos(2xx) 2 d </